ANALYSIS OF FINANCIAL PERFORMANCE DEVELOPMENT OF PT. JAPFA COMFEED INDONESIA TBK REGISTERED ON THE INDONESIA STOCK EXCHANGE (PERIOD 2021-2023) - Nurul Maqfirah Putri Nurman; Haeril Haeril; Jumria Basri (Journal Of Accounting And Finance, 2025)
This study aims to analyze how the development of financial performance at PT. Japfa Comfeed Indonesia Tbk. This study uses a quantitative method, namely data presented in the form of numbers. The results of this study indicate that the company's financial condition is not good. Because PT. Japfa Tbk recorded sales of IDR 11.76 trillion in the first quarter of 2023. These sales fell 3.22% compared to the same period last year of IDR 12.15 trillion. Based on JAPANFA's financial report released on Thursday (27/4), the decline in sales caused the commercial livestock segment to plunge 3.69% to IDR 4.49 trillion. The livestock processing and consumer product segments fell 0.09% to IDR 1.84 trillion.